India fast forward - Vakil, Tarjani (Bombay Export-Import Bank of India, 1996)
Contributed articles on India's foreign trade and investment policy reforms.
Keywords: Investments, Foreign -- India; Investments, Foreign -- Government policy -- India; Industrial policy -- India; Technology transfer -- India